2013
DOI: 10.1136/bjophthalmol-2013-303758
|View full text |Cite|
|
Sign up to set email alerts
|

Sebaceous carcinoma in Japanese patients: clinical presentation, staging and outcomes

Abstract: In this Japanese cohort, an eyelid mass was the main clinical presentation of sebaceous carcinoma. Contrary to previous reports, T2a tumours smaller than 10 mm were associated with regional nodal metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 17 publications
6
44
0
Order By: Relevance
“…The Indian cohort also found that the risk of systemic metastasis and death was related to an increasing T category 9. However, in the Japanese cohort, the authors found that tumours even smaller than T2a were associated with tumour metastasis 8. This may be because of the difference in the primary modality of treatment employed.…”
Section: Discussionmentioning
confidence: 97%
“…The Indian cohort also found that the risk of systemic metastasis and death was related to an increasing T category 9. However, in the Japanese cohort, the authors found that tumours even smaller than T2a were associated with tumour metastasis 8. This may be because of the difference in the primary modality of treatment employed.…”
Section: Discussionmentioning
confidence: 97%
“…Watanabe et al . reported two of 37 sebaceous carcinomas with primary T2a tumors measuring 5 mm and 7 mm, respectively, developed nodal metastases during follow up . This result shows that even small lesions present a risk of metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Nodal metastases were seen in 8% of the patients, with preauricular being the predominant site. The primary tumor with the stage of T3a or greater has been significantly associated with local recurrence . The locally aggressive nature of sebaceous carcinoma has been reported .…”
Section: Discussionmentioning
confidence: 99%